DESIGNING CONSTRUCTIVE TOYS TO FOSTER GEOMETRIC EXPLORATION IN EARLY CHILDHOOD EDUCATION - Evilya Meyliana Purwanto Putri; Nurul Fitriana Bahri; Asep Sufyan Muhakik Atamtajani (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
During the ages of 4 to 6, children experience substantial growth and development. Interaction with their surroundings becomes a crucial catalyst for their cognitive development. Constructive beam play emerges as an effective medium, but its limitations can diminish children’s interest. This study endeavors to design innovative beam gaming tools that cater to the needs and preferences of 4-6 year olds and facilitate their optimal development. The research methodology employed involves qualitative methods guided by a user-centered design approach. The resulting final design emerges as a potent tool capable of strengthening various aspects of children’s development. These measures underscore the paramount importance of incorporating children’s needs and preferences into the design process. By doing so, the final product becomes more pertinent and suitable for children’s use. The culmination of this study yielded a constructive beam APE design that incorporates safety materials. Additionally, it encompasses a constructive system specifically designed for children aged 4 to 6. Furthermore, the child demonstrated focus and problem-solving abilities during the duration of each instruction and the use of playing cards.